Evaluating Diverse Solar Irrigation Systems for their Scalability in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Solar irrigation systems offer a climate-smart and sustainable approach to extend the area under irrigation while using a renewable source of energy. They strive to break the vicious cycle of excessive green-house gas emissions (GHG) due to the usage of electricity or diesel operated pumps, which further exacerbates the vulnerabilities of farmers, pushing them to engage in resource intensive farming practices. In India, there is a predominance of electric or diesel operated pumps in the agricultural irrigation space. However, with increasing focus on solar energy’s use in agriculture in recent times, several pilots and models on solar irrigation systems have been rolled out in the country. Nevertheless, the scaling of solar irrigation mechanism has been fraught with challenges despite heavy subsidies being provided to the farmers for its promotion. This rationales the need to comprehensively synthesise such pilots leading to the identification of efficient and effective models for scaling. It is also imperative to evaluate different business and institutional models of solar irrigation systems to understand factors supporting and hindering their adoption. With this vision of generating a comprehensive knowledge base on different functional solar powered smart irrigation models in India and their scalability, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), Borlaug Institute of South Asia (BISA)-International Maize and Wheat Improvement Center (CIMMYT) is documenting and evaluating different solar pump models across India, in collaboration with the Deutsche Gesellschaft für Internationale Zusammenarbeit GmbH (GIZ) and International Water Management Institute (IWMI).